Clinical analysis of Shengxuening combined with levocarnitine for renal anemia in hemodialysis patients - LIU Ying-shuang; ZHANG Yu-mian; WANG Shu-zhen; WANG Xiao-qing (Linchuang shenzangbing zazhi)
Objective To investigate the efficacy of Shengxuening tablets combined with Levocarnitine in treatment of renal anemia.Methods Ninety-six cases of maintenance hemodialysis(MHD)patients were randomly divided into three groups,given withfolic acid and vitamin B12,and subcutaneous injection of recombinant human erythropoietin(EPO) as the basic treatments.Additionally,the patients in group A were given Shengxuening tablets(0.5 g,three times every day) and levocarnitine(intravenous injection of 1 g dissolved in 2 mL normal saline for 3- 5 min).The patients in group B were given ferrous succinate(0.2 g,3 times every day) and levocarnitine.The patients in group C were given ferrous succinate(0.2 g,3 times every day).During the treatment course,other ferrous reagents and drugs influencing iron metabolism were not administered.After consecutive treatment for12 weeks,the efficacy was observed.Results After treatment,hemoglobin(Hb),hematocrit(Hct),serum iron(SI),total iron binding force(TIBC),serum ferritin(SF),and transferrin saturation(TSAT) were significantly increased in all groups as compared with those before treatment(P<0.05).After treatment for 3 months,Hb,Hct,SI,TIBC,SF and TSAT in group A were significantly higher than in group B(P<0.05).The usage of EPO in all groups was significantly reduced after treatment as compared with that before treatment(P<0.05).The dosage of EPO in group A was significantly less than that in groups B and C(P<0.05).Conclusions The combined use of Shengxuening with levocarnitine for renal anemia in MHD patients can significantly improve the anemia state,reduce the incidence of adverse reactions,and increase the dosage of EPO.